Increased Anion Gap Metabolic Acidosis as a Result of 5- Oxoproline (Pyroglutamic Acid) in Pregnancy: A Case Report - Sathiyathasan, S; Jeyanthan, K; Soper, H; Hamid, R (Nepal Journal of Obstetrics and Gynaecology, 2014)
Accumulation of 5- Oxoproline (pyroglutamic acid) is a rare cause of severe, high anion gap metabolic acidosis in adults. A 21 year old lady presented at 39 weeks gestation in her first pregnancy with 2 weeks history of shortness of breath. Arterial blood gas showed metabolic acidosis. Urine and serum samples were taken which showed an increase in the serum level of 5- Oxoproline -creatinine ratio indicating pyroglutamic metabolic acidosis. Metabolic acidosis that is caused by 5- oxoproline results from disruption of the gamma glutamyl cycle. Glutamile synthetase (GS) deficiency is an autosomol recessive disorder. With GS deficiency, reduced glutathione levels increases gamma glutamile synthetase activity, and the resulting gamma - glutamile cystine levels are converted to 5-oxoproline.Suspicion for 5-oxoproline-associated high anion gap metabolic acidosis should be made when the cause of high anion gap metabolic acidosis remains poorly defined. DOI: http://www.dx.doi.org/10.3126/njog.v7i2.11144 Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 2 / Issue 14 / July-Dec, 2012 / 47-49